Mampukah Corporate Governance Mengurangi Eksekutif Risk Taker Melakukan Penghindaran Pajak? - Noviari, Naniek; Agung Suaryana, I Gusti Ngurah (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 2 (2019), 2019)
Taxpayers will try to pay the smallest possible tax. One way to reduce taxes is to take tax avoidance actions or commonly called tax avoidance. One of the causes of this practice is the executive character who dares to take risks. The impact of the executive character on tax resignation can be reduced by the implementation of good corporate governance. This research proposes the application of good corporate governance to reduce the impact of the executive character on aggressive tax actions. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange in 2014-2016. Sampling using purposive sampling. The number of research samples was 48 observations. This study involved one independent variable (executive characteristics), one dependent variable (aggressive tax action), and one corporate governance variable. The study used moderated regression analysis (MRA). This study found the more aggressive the executive character, the higher the tax avoidance action. The better the implementation of good corporate governance, the lower the tax avoidance action. The better the implementation of good corporate governance, weakening the influence of executive character on tax avoidance actions.   Keywords : tax avoidance, executive characteristics, good corporate governance.